Return on Investment in Mining Companies: Intellectual Capital Aspect - Rita Martini; Sulaiman Sulaiman; Maria Maria; Kartika Rachma Sari; Lambok Vera Riama Pangaribuan; Hanina Sari (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This research to know the relationship between intellectual capital and financial performance as measured by return on investment (ROI) using financial statement data for the period 2012-2016 from mining companies listed in the Indonesia Stock Exchange (IDX). The measurement model Intellectual Capital use Pulic’s model with Value Added Intellectual Coefficient, which are a component of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA). The analysis used was multiple linear regression. The results of the hypothesis test showed that VACA, VAHU and STVA together significantly effect to ROI. The results showed, STVA and VACA significant effect to ROI, while variable VAHU no significant impact to ROI because it being economic downturn that led to the mining business become lethargic. Further research can add a number of samples or a longer period because the result of this research is limited only 6mining companies into the samples, so that future studies can provide a more perfect. Suggested to reexamine variables during stable economic condition to prove the possibility result which different with this research.